ISTIBDAL WAKAF DALAM PANDANGAN FUKAHA KLASIK DAN KONTEMPORER - Atep Waluya (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2018)
Wakaf management errors are not uncommon in the community. This is sometimes due to a lack of understanding about the jurisprudence of wakaf. Among the mismanagement of waqf management that is not uncommon in the community is the implementation of wakaf istibdal. Fukaha agreed basically that wakaf should not be traded. But when the waqf is not useful then according to some fukaha may be sold to be replaced with the like with it. Similarly also according to some jurists may istibdal wakaf to the more useful and maslahat of the diakadkan, but kekemaslahatan should be based on the government's perspective or Wakaf Board of Indonesia.